Improving government's response to local communities - is place management an answer? - Walsh, Peter (2001)
The notion of place management is emerging in public sector discourse as a potential solution to improve governments' responses to issues confronting local communities, particularly those experiencing high levels of economic and social disadvantage. Despite the increased currency of the term, there is a degree of confusion surrounding what it actually means. And it is not always clear what is meant by the notion of `place'. This article attempts to clarify a working definition of `place management' and to explore the policy and administrative implications for governments in adopting a place management approach. - Reproduced
Keywords: Management; Public administration